PENGGUNAAN MEDIA PUZZLE DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI PECAHAN MATA PELAJARAN MATEMATIKA - Daud, Sul Min; Otaya, Lian Gafar; Huljannah, Miftha (DIRASATUL IBTIDAIYAH, 2024)
This puzzle media functions as an intermediary to convey mathematics material so that it is easily understood by elementary school students. Therefore, researchers conducted research on the use of puzzle media in improving student learning outcomes in class III mathematics subjects at SDN 9 Limboto. This research aims to find out whether the use of puzzle media can improve student learning outcomes in Mathematics class III 9 Limboto. The research model used is classroom action research by Kemmis Mc Tagart. The research subjects were 16 class III students at SDN 9 Limboto. The data collection technique is in the form of a test to determine the level of student understanding of the material, observation to determine student activity in implementing the learning process, while documentation is used to collect data that is relevant to research. The research results show that in the initial conditions based on the pretest results, 20% of students had reached the KKM, while 80% of students had not yet reached the KKM. Then in the cycle there was a very significant increase, namely 85% of students had reached the KKM while 15% of students had not reached the predetermined KKM. This proves that the use of puzzle media in mathematics learning can improve the learning outcomes of class III students at SDN 9 Limboto.Keywords: Learning Outcomes, Use of Puzzle Media, Fraction MaterialMedia puzzle ini berpungsi sebagai perantara untuk menyampaikan materi matematika agar mudah dipahami oleh siswa SD oleh karna itu peneliti melakukan penelitian penggunaan media puzzle dalam meningkatkan hasil belajar siswa pada mata Pelajaran matematika kelas III SDN 9 Limboto. Penelitian ini bertujuan untuk mengeetahui apakah penggunakan media puzzle dapat meningkatkan hasil belajar siswa mata Pelajaran matematika kelas III 9 Limboto. Model penelitian yang digunakan yaitu penelitian Tindakan kelas oleh kemmis mc tagart. Subjek penelitian yakni siswa kelas III SDN 9 Limboto yang berjumlah 16 orang. Adpaun Teknik pengumpulan data berupa tes untuk mengetahui Tingkat pemahaman siswa terhadap materi, obervasi untuk mengetahui qktivitas siswa dalam pelaksanaan proses pembelajaran, sedangkan domentasi sebagai pengumpul data yang relevansi dengan penelitian. Hasil penelitian menunjukan bahwa pada akondisi awal berdasarkan hasil preetest yakni 20 % siswa sudah mencapai KKM sedaangkan 80% siswa yang belum mencapai KKM. Kemudian pada siklus terjadi peningkatan yang sangat signifikan yaitu 85% siswa sudah mencapai KKM sedangkan 15% siswa belum mencapai KKM yang sudah ditetapkan. Hal ini membuktikan bahwa penggunaan media puzzle dalam pembelajaran matematika dapat meningkatkan hasil belajar siswa kelas III SDN 9 Limboto.Kata Kunci: Hasil Belajar, Penggunaan Media Puzzle, Materi Pecahan